LECTURER PERFORMANCE MODEL: COMPENSATION, WORK DISCIPLINE AND ORGANIZATIONAL COMMITMENT ANALYSIS (Case Studi in Universitas Putra Indonesia YPTK Padang) - Rizki Mulyani, Siti (Dinasti Publisher, 2020)
This study aims to determine the effect of compensation, work discipline and organizational commitment on the performance of the lecturer at Putra Indonesia University YPTK Padang. This research was conducted at the Putra Indonesia University YPTK Padang. The population in this study were all lecturers at the University of Indonesia Putra Indonesia YPTK Padang. The sample in this study were 50 people with porposional techniques. Types and sources of research data consist of primary data that is data obtained from the opinions of respondents through research questionnaires, and secondary data that is data obtained from the University of Putra Indonesia YPTK Padang Data analysis techniques used in testing the research hypothesis are multiple linear regression analysis using SPSS version 17.0 program. The results found that: 1) compensation had a positive and significant effect on the performance of the University of Putra Indonesia YPTK Padang lecturers; 2) Work discipline has a positive but not significant effect on the performance of the Indonesian Putra University YPTK Padang lecturer; 3) Organizational Commitment has a positive and significant effect on the performance of the University of Putra Indonesia YPTK Padang lecturers; and 4) Compensation, work discipline and organizational commitment together have a significant effect on the performance of the lecturer at Putra Indonesia University YPTK Padang with a contribution of 46% and the remaining 54% is influenced by other factors not included in the scope of this study.